2017
DOI: 10.2118/179684-pa
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Low-Interfacial-Tension Imbibition in Oil-Wet Carbonates

Abstract: Summary Primary and secondary oil recovery from naturally fractured oil-wet carbonate reservoirs is very low. Enhanced oil recovery (EOR) from these reservoirs by use of surfactants to alter the wettability and reduce the interfacial tension (IFT) has been extensively studied for many years, but there are still many questions regarding the process mechanisms, surfactant selection and testing, experimental design, and, most importantly, how to scale up the laboratory results to the field. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…Injector wells to the left and right of the core and a producer well at the top of the container flow at a rate of 0.5 pore volumes per week to recover the produced fluids and maintain the test solution concentration in the container. This flushing rate is approximately that used by Li et al (2017).…”
Section: Simulation Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Injector wells to the left and right of the core and a producer well at the top of the container flow at a rate of 0.5 pore volumes per week to recover the produced fluids and maintain the test solution concentration in the container. This flushing rate is approximately that used by Li et al (2017).…”
Section: Simulation Resultsmentioning
confidence: 93%
“…The produced oil can be more difficult to quantify if the surfactant solution forms emulsions. Li et al (2017) used modified static imbibition cells where the produced emulsions were periodically displaced from the cell with fresh surfactant solution and the emulsions were separated to better quantify the oil recovery. They systematically evaluated different chemical formulations and core dimensions to better understand the process mechanisms and how to scale up the experimental results from the lab to the field using an improved scaleup group.…”
Section: Experimental Investigation Of Wettability Alterationmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the reservoirs with an average permeability of >0.3 mD can be developed by water flooding, but their ultimate recovery factor is less than 10%. In recent few years, many researchers have been working actively on the ways to improve water flooding, such as surfactant injection and nanofluid injection. Previous research studies indicated that the oil displacement efficiency depends mainly on the imbibition effect generated by capillary force during water flooding of the tight reservoir. , However, the existing surfactants are mostly micron-sized, making them fail to efficiently enter the pores and throats of the tight reservoir matrix. Thus, the field injection–production relationship fails to be built, resulting in serious imbalance of injection and production.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, numerous efforts have been devoted to further reduce the IFT between oil and water. Current technologies enable very low IFTs (10 –1 –10 –2 mN/m) or even ultralow IFTs (≤10 –3 mN/m). In some cases, however, the performance is still below expectation, even if an ultralow IFT is reached. At present, another voice in academia is stating that emulsification should be considered as the major function of surfactant flooding.…”
Section: Introductionmentioning
confidence: 99%